SOFTWARE AND HARDWARE PLATFORM FOR DEPLOYMENT OF THE DIGITAL TWINS IOT SYSTEMS USING BLOCKCHAIN TECHNOLOGY - KHOMIAK, VITALII; MISHAKIN, MAKSYM; DUMYCH, STEPAN; ANDRUSHCHAK, VOLODYMYR; MAKSYMYUK, TARAS (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article outlines the development of an interactive IoT system based on digital twin technology, implemented on the Home Assistant platform with 3D visualization in Unreal Engine. The study focuses on creating accurate digital representations of physical objects and achieving real-time synchronization using IoT sensors, the MQTT protocol, and edge computing. The implementation process includes 3D scanning of physical spaces, optimizing 3D models, integrating sensor data, and configuring interactive scenarios for managing IoT devices. The system is designed for visual monitoring, process automation, and integration into the Metaverse. The results confirm the effectiveness of this approach for managing IoT systems and improving automation, offering new opportunities for deploying digital twins in large-scale IoT networks and smart environments.